Nanocarriers for drug delivery : liposomes and polymersomes - Lee, Ru Xuan (2016)
According to the World Health Organization (WHO), glaucoma is the world’s second leading cause of blindness and it can affect anyone from any race, gender and age. Current treatment methods for glaucoma include the use of topical daily eye drops, laser therapy and surgery. Topical daily eye drop is often used in glaucoma treatment. However less than 5% of the drug permeates and enters the eye due to the physiological and anatomical of eye barriers. Hence it usually leads to suboptimal control of intraocular pressure (IOP) and poor patient compliance. To overcome these drawbacks, sustained drug delivery is warranted that could be beneficial for ocular diseases such as glaucoma. In this project, liposomes and polymersomes are synthesized as nanocarriers and its loading capability is explored and will be evaluated in in-vitro conditions. Three different lipids are used to formulate liposomes which are then loaded with varying concentrations of latanoprost drug. Their size stability and release profiles are then studied and compared. Loading capability of polymersomes is also explored using 5(6)-carboxyfluorescein (CF) dye. The size and morphology of the CF-loaded polymersomes as well as its release profile are studied. Liposomes have shown promising results for sustained delivery while more studies are require to determine and understand the optimal conditions for loading and sustained drug delivery using polymersomes.